2007
DOI: 10.5713/ajas.2007.1587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy Density on Growth, Carcass Quality and mRNA Expression of Fatty Acid Synthase and Hormone-sensitive Lipase in Finishing Pigs

Abstract: A single factorial experiment was conducted to test the effects of three dietary levels of energy on mRNA expression of fatty acid synthase (FAS-mRNA) and hormone-sensitive lipase (HSL-mRNA) and their association with intramuscular fat in finishing pigs. 72 crossbred (Large White×Rongchang) barrows with an average initial body weight of 20.71 (s.e. 0.1) kg, were randomly allotted to three dietary treatments (11.75, 13.05 and 14.36 MJ DE/kg) and fed until slaughtered at 100 or 101 kg. The diets were iso-nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
4
16
1
Order By: Relevance
“…2. Liu et al [17] reported increased weight gains when the dietary energy increased which is similar to the results of Du et al [18]. Similar to the current study, De La Llata et al [9] found pigs fed high energy levels had a significantly improved weight gain only during the growing stage and not during the finishing stage.…”
Section: Resultssupporting
confidence: 90%
“…2. Liu et al [17] reported increased weight gains when the dietary energy increased which is similar to the results of Du et al [18]. Similar to the current study, De La Llata et al [9] found pigs fed high energy levels had a significantly improved weight gain only during the growing stage and not during the finishing stage.…”
Section: Resultssupporting
confidence: 90%
“…The downregulated expression of these lipolysis genes and protein expression means there is an increased capacity of LM for de novo synthesis of FFA, leading to increasing IMF accumulation. Similar results were previously observed by Liu et al (2007) and Peng et al (2012). Liu et al (2007) researched the effects of three dietary energy treatments on mRNA expression of HSL in finishing pigs, results showed that the correlations between HSL mRNA and dietary energy or IMF were negative.…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al. () researched the effects of three dietary energy treatments on mRNA expression of HSL in finishing pigs, results showed that the correlations between HSL mRNA and dietary energy or IMF were negative. Peng et al.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the energy content of the diet, results usually in improved FCR (Smith et al, 1999;Quiniou and Noblet, 2012), increased BF depth, and often in an increase in the IMF content of pork meat (King et al, 2004;Liu et al, 2007).…”
Section: Ajinomoto 2017mentioning
confidence: 99%
“…An increase in energy content of the diet results usually in improved feed efficiency (Smith et al, 1999;Quiniou and Noblet, 2012) and increased BF depth and IMF content of pork meat (King et al, 2004;Liu et al, 2007). However, the beneficial effects of increasing the NE content of the diet on ADG are less consistent (Matthews et al, 2003;Quiniou and Noblet, 2012;Coca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%